Investigation of substrate selection and finishing protocols for nursery container production of 13 plant taxa native to the southwestern United States - Linfield, Allisa, author; Bousselot, Jennifer, advisor; Gu, Mengmeng, committee member; Davis, Jessica, committee member; Shonle, Irene, committee member (Colorado State University. Libraries, 2023)
Nursery-produced native plant taxa are a tool for habitat restoration, and their use extends beyond wildlife areas as urban residents seek to create wildlife corridors. Water conservation concerns and understanding of pollinator decline further motivates use of native plants in cultivated and designed landscapes. Furthermore, increasing awareness around degradation of peatlands, drives consumer interest in sustainably produced plant material using peat-alternative substrates. Growers attempt to meet the demand for native plant material, but protocols for growing these taxa, which are not adapted to thrive in peat-based substrates, are limited. Without finishing protocols for sizing up propagules to retail size, growers, who are limited by time and resources, amend peat-based substrates using trial and error in hopes of achieving favorable growing outcomes. We identified grower practices through a survey of nationwide Plant Select® growers. Based on survey results, we evaluated survivability and plant growth in response to partially replacing peat-based substrate with sand, field soil, a microbial-inoculated compost (MIC), and a green waste compost (GWC). Our results indicated that plant growth response to these substrates is taxon specific. However, only one of the 13 taxa evaluated resulted in a significantly higher plant growth index (PGI) increase in the control group. Thus, our findings suggest that 12 of the investigated taxa may respond to peat-reduced substrates during the finishing period without significant negative impacts on PGI or dry weight.
Keywords: nursery container production; substrates; native plants; sustainable; peat-alternatives